Peran Syekh Abdul Wahab Lubis dalam Penyebaran Islam di Mandailing Natal, 1919-1991 - Lubis, Intan Ali; Achiriah, Achiriah (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
Sheikh Abdul Wahab Lubis, a prominent Islamic scholar from Mandailing Natal, specifically Muara Mais, played a crucial role in the propagation of Islam in the region. This study delves into the biography and contributions of Sheikh Abdul Wahab Lubis in spreading Islam throughout Mandailing Natal. Utilizing a qualitative research methodology, data were gathered through observation, interviews, and documentation. Born in 1919 and passing away in 1991, Sheikh Abdul Wahab Lubis was well-versed in Islamic jurisprudence. His efforts to disseminate Islam were executed through direct community engagement and educational initiatives, notably by establishing the Darul Ulum Islamic boarding school in Muara Mais. This institution not only provided religious education but also became a center for community development and spiritual guidance. This research provides valuable insights into Sheikh Abdul Wahab Lubis's significant contributions to reinforcing Islamic teachings, fostering religious education, and nurturing the younger generation through his pesantren, thereby leaving a lasting legacy in Mandailing Natal.